PERBEDAAN EFEKTIVITAS BERMAIN PAPAN TEMPEL DAN PLAYMATE DALAM MENINGKATKAN PENGETAHUAN TENTANG PEMELIHARAAN KESEHATAN GIGI DAN MULUT PADA SISWA TK - Rahmawati, Klarisa; Mulyanti, Sri; Fatikhah, Nurul; Laut, Deru Marah (Poltekkes Kemenkes Bandung, 2025)
Maintaining dental and oral hygiene is one of the efforts to improve dental and oral health. Children must be taught from an early age to have healthy teeth. One appropriate method for providing education to young children is by playing with stick boards and playmates. The aim of this research was to determine the difference in effectiveness between playing with stick boards and playmates in increasing knowledge of dental and oral health maintenance among Kindergarten Plus Tunas Bangsa students. This research method uses a quasi-experiment with a two group pretest posttest design. Sampling was carried out using a total sampling technique with the number of respondents in this study being 34 students. The data analysis technique uses the Wilcoxon test to determine the effect of the two media on maintaining dental health and the Mann Whitney test to see the difference in effectiveness between the sticky board and playmate media on maintaining dental and oral health. The results of the research show that there is a difference in effectiveness between playing with stick boards and playmates in increasing knowledge of maintaining oral health with the results of the Mann Whitney test getting a value of p=0.000 (p<0,05). It can be concluded that sticky board media is more effective for kindergarten students to use than playmate media.